Steel sheet, member, and method for producing same
By controlling the composition and microstructure of the steel plate, the problems of reduced ductility and extension flange forming of high-strength steel plate during stamping and forming are solved, and the steel plate with high strength, excellent forming and material stability are achieved.
Patent Information
- Application Number
- CN202380064564.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-22
AI Technical Summary
During stamping, existing high-strength steel plates are prone to problems such as decreasing ductility, decreasing extension flange forming and fluctuating material stability in the direction of plate width, resulting in a decrease in yield and damage to dimensional accuracy.
By controlling the composition and microstructure of the steel plate, the area ratio of polygonal ferrite is ensured to be more than 10% and less than 57%, the total area ratio of upper bainite and tempered martensite is more than 40% and less than 80%, the volume ratio of residual austenite is more than 3% and less than 15%, and the total area ratio of quenched martensite and residual austenite is controlled to be less than 20%, so as to obtain excellent stamping forming, ductility and extension flange forming, and improve material stability in the plate width direction.
A high-strength steel plate with a tensile strength of more than 980MPa has been achieved, with excellent stamping forming, ductility and extension flange forming, and material stability is shown in the direction of the plate width, which improves yield and reduces environmental load.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a steel plate, a component and a method for manufacturing the same. More specifically, the present invention relates to a steel plate, a component and a method for manufacturing the same having a tensile strength (TS) of 980 MPa or more, excellent formability and material stability. The steel plate of the present invention is suitable as a raw material for a frame component for an automobile. Background Art
[0002] In recent years, from the perspective of protecting the global environment, the strengthening of CO2 emission gas restrictions for automobiles is being carried out in the international framework. In order to improve the fuel efficiency of automobiles, the most effective way is to reduce the weight of automobile bodies by thinning the steel plates used for automobile frame components. Therefore, in order to contribute to the low fuel efficiency of automobiles, the use of high-strength steel plates is increasing. However, with the high strength of steel plates, cracks are easily generated during stamping due to reduced ductility and reduced stretch flange formability. Therefore, steel plates with better ductility and stretch flange formability than before are desired.
[0003] In addition, from the perspective of carbon neutrality, material exhaustion (yield improvement) is required, and excellent material stability in the width direction of the steel plate is also required. However, with the high strength of the steel plate, the fluctuation of formability such as ductility and hole expansion in the width direction of the plate becomes significant, and cracks are easily generated during stamping. Therefore, it is necessary to set restrictions on the blanking position, which has the problem of reduced yield.
[0004] In addition, generally, as the strength increases, the yield ratio: YR (YR=yield strength YS / tensile strength TS) increases, which causes a problem of increased springback after forming.
[0005] As a technology to improve the formability of high-strength steel sheets, TRIP steel sheets with retained austenite dispersed in the structure have been developed. For example, Patent Document 1 discloses that by annealing a steel containing 0.04-0.12% C, 0.8-2.5% Si, and 0.5-2.0% Mn, austenite tempering (carbon distribution accompanied by bainite transformation) is maintained at 300-500°C for 10-900 seconds to generate 2-10% retained γ, thereby obtaining a steel sheet with high ductility of TS×El≥21000MPa·% and high elongation flange formability of more than 70%.
[0006] In addition, Patent Document 2 discloses the following technology: temporarily cooling to a temperature range between the martensitic transformation start temperature (Ms point) and the martensitic transformation end temperature (Mf point) during the cooling process, and then reheating and holding to stabilize the retained austenite, and utilizing the principle of so-called Q&P: Quenching & Partitioning (quenching and carbon distribution from martensite to austenite) to achieve high ductility of the steel sheet. Specifically, the following steel sheet and its manufacturing method are disclosed: a cold-rolled steel sheet having a predetermined chemical composition is held at a first soaking temperature of 750°C or higher, cooled to a cooling stop temperature in a temperature range of 150 to 350°C, and then reheated to a temperature range of 350 to 500°C, thereby ensuring a retained austenite of 5 to 15% by volume fraction, taking into account both a TS of 980 MPa or higher and a ductility of 17% or higher, and having excellent hole expansion with a hole expansion rate of 50% or higher.
[0007] On the other hand, DP steel (dual phase steel) has been developed as a steel sheet with a low yield ratio that is effective in reducing springback. General DP steel is a multiphase steel in which martensite is dispersed in a ferrite structure as a main phase, and has a high TS, a low yield ratio, and excellent ductility. However, stress is concentrated on the interface between ferrite and martensite, which easily causes cracks, so DP steel has the disadvantage of poor stretch flange formability. As a technology for improving the stretch flange formability of DP steel, there are, for example, Patent Document 3 and Patent Document 4.
[0008] Patent document 3 discloses the following technology: by controlling the occupancy factor of ferrite relative to the entire structure to be 50% or more, the occupancy factor of martensite to be 3 to 30%, and the average grain size of ferrite to be 10 μm or less, and the average grain size of martensite to be 5 μm or less, the deterioration of stretch flange formability is suppressed.
[0009] In addition, Patent Document 4 discloses that by controlling the occupancy factor of ferrite relative to the entire structure to 5 to 30% and the occupancy factor of martensite to 50 to 95%, the ferrite is controlled to be fine with an average grain size of less than 3 μm in equivalent circle diameter and the martensite has an average grain size of less than 6 μm in equivalent circle diameter, thereby improving ductility and stretch flange formability.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent No. 5515623
[0013] Patent Document 2: Japanese Patent No. 5821911
[0014] Patent Document 3: Japanese Patent No. 3936440
[0015] Patent Document 4: Japanese Patent Application Publication No. 2008-297609 Summary of the invention
[0016] Problems to be solved by the invention
[0017] Although the above-mentioned Patent Documents 1 and 4 disclose methods for manufacturing steel plates with excellent ductility and stretch flange formability, it is necessary to form a large amount of soft phase ferrite, so it is difficult to achieve high strength of, for example, 780 MPa or more. In addition, although Patent Document 2 has excellent ductility and stretch flange formability, since it is a steel plate with a YR of 0.8 or more, the dimensional accuracy is sometimes impaired due to springback during stamping. In addition, Patent Document 3 discloses a method for manufacturing a DP steel plate with low YR and excellent stretch flange formability, but since it is a DP structure, the ductility is not necessarily sufficient. In addition, none of the patent documents discloses a technology for suppressing fluctuations in ductility and stretch flange formability in the plate width direction. Therefore, it is required to develop a high-strength steel plate that has excellent material stability in the plate width direction in addition to excellent ductility and excellent stretch flange.
[0018] In view of the above situation, the object of the present invention is to provide a steel plate, a component and a method for manufacturing the same having a tensile strength (TS) of 980 MPa or more, excellent stamping formability, ductility and stretch flange formability, and excellent material stability in the plate width direction.
[0019] Here, the tensile strength refers to the tensile strength (TS) obtained in accordance with JIS Z2241 (2011).
[0020] Excellent stamping properties means that the yield ratio YR obtained in accordance with JIS Z2241 (2011) is 0.8 or less.
[0021] Excellent ductility means that the total elongation EL obtained in accordance with JIS Z2241 (2011) satisfies any one of the following (A) and (B).
[0022] (A) When TS is 980 MPa or more and less than 1180 MPa, EL is 14.0% or more;
[0023] (B) When TS is 1180 MPa or more, EL is 12.0% or more.
[0024] Excellent stretch flange formability means that the hole expansion ratio λ(%) (={(d-d0) / d0}×100) obtained by a hole expansion test specified in JFST1001 is 40% or more.
[0025] Excellent material stability in the board width direction means that the board width of region A that continuously satisfies the following equations (1) and (2) with respect to EL and λ at the measurement position X in the board width direction accounts for 80% or more of the total board width.
[0026] -10≤100×[(EL(%) at measurement position X in area A - EL(%) at center of board width) / EL(%) at center of board width]≤10 …(1)
[0027] -10≤100×[(λ(%) at measurement position X in region A - λ(%) at center of plate width) / λ(%) at center of plate width]≤10 …(2)
[0028] (In the formulas (1) and (2), the measurement positions X are set to a total of 23 locations of the 24 division positions of the plate width W of the steel plate (the contact locations of the adjacent widths of the 23 locations when the plate width W is divided into 24 equal widths). That is, as the positions in the plate width direction, W / 24, 2W / 24, 3W / 24, 4W / 24, 5W / 24, 6W / 24, 7W / 24, 8W / 24, 9W / 24, 10W / 24, 11W / 24, 12W / 24, 13W / 24, 14W / 24, 15W / 24, 16W / 24, 17W / 24, 18W / 24, 19W / 24, 20W / 24, 21W / 24, 22W / 24, and 23W / 24, a total of 23 locations are set as the measurement positions X.)
[0029] Here, for example, when the measurement position X that continuously satisfies equations (1) and (2) is 2W / 24 to 20W / 24, the plate width of region A that continuously satisfies equations (1) and (2) is 100×(20-2+1) / 23=83% of the total plate width.
[0030] Methods used to solve problems
[0031] In order to solve the above-mentioned problems, the inventors have conducted in-depth research on various factors affecting stamping formability, ductility, stretched flange formability and material stability from the perspectives of the component composition, microstructure and manufacturing conditions of various thin steel plates with a tensile strength of more than 980 MPa. As a result, it was found that by containing, in mass%, C: 0.05-0.20%, Si: 0.40-1.50%, Mn: 1.9-3.5%, P: 0.02% or less, S: 0.01% or less, sol.Al: 0.005-0.50%, N: less than 0.015%, and forming a C-rich region (S-rich region) with a C concentration of 0.5 mass% or more, the area ratio of polygonal ferrite is 10% or more and 57% or less, the total area ratio of upper bainite, tempered martensite and lower bainite is 40% or more and 80% or less, the area ratio of retained austenite (retained γ) is 3% or more and 15% or less, the area ratio of quenched martensite is 12% or less (including 0%), the total area ratio of quenched martensite with an aspect ratio of 3 or less and an equivalent circle diameter of 1.6 μm or more and retained γ is 20% or less, and the C concentration is 0.5 mass% or more. C≥0.5 ) relative to the overall area ratio of the steel structure is less than 15%, it is possible to obtain a high-strength cold-rolled steel sheet having excellent stamping formability, ductility and stretched flange formability, and further having excellent material stability in the width direction of the plate (small material fluctuation).
[0032] The present invention has been accomplished based on the above findings, and the gist of the present invention is as follows.
[0033] [1] A steel plate having:
[0034] A composition containing, in mass%, C: 0.05-0.20%, Si: 0.40-1.50%, Mn: 1.9-3.5%, P: 0.02% or less, S: 0.01% or less, sol.Al: 0.005-0.50%, N: less than 0.015%, and the balance being iron and inevitable impurities; and
[0035] The area ratio of polygonal ferrite is 10% to 57%, the total area ratio of upper bainite, tempered martensite and lower bainite is 40% to 80%, the volume ratio of retained austenite is 3% to 15%, the area ratio of quenched martensite is 12% or less (including 0%), and the remaining structure is composed of the remaining structure.
[0036] The total area ratio of quenched martensite and retained austenite with an aspect ratio of 3 or less and an equivalent circle diameter of 1.6 μm or more is 20% or less relative to the total area ratio of quenched martensite and retained austenite.
[0037] The C-rich region (SC≥0.5 ) is less than 15% in area.
[0038] [2] The steel sheet according to [1], further comprising, as the above-mentioned component composition, one or two selected from the group consisting of Ti: 0.1% or less and B: 0.01% or less in mass %.
[0039] [3] The steel sheet according to [1] or [2], further comprising, as the above-mentioned component composition, one or more selected from the group consisting of Cu: 1% or less, Ni: 1% or less, Cr: 1% or less, Mo: 0.5% or less, V: 0.5% or less, and Nb: 0.1% or less.
[0040] [4] The steel sheet according to any one of [1] to [3], further comprising, as the above-mentioned component composition, one or more selected from the group consisting of Mg: 0.0050% or less, Ca: 0.0050% or less, Sn: 0.1% or less, Sb: 0.1% or less, and REM: 0.0050% or less in terms of mass %.
[0041] [5] The steel sheet according to any one of [1] to [4], having a zinc plating layer on the surface.
[0042] [6] A member formed using the steel plate according to any one of [1] to [5].
[0043] [7] A method for producing a steel sheet, comprising hot rolling, pickling and cold rolling a steel slab having the composition described in any one of [1] to [4], and then annealing the obtained cold-rolled steel sheet, wherein:
[0044] The above annealing includes:
[0045] A holding step, wherein the cold-rolled steel sheet is heated to an annealing temperature of 750 to 880° C. and held at the annealing temperature for 10 to 500 seconds;
[0046] A first cooling step, wherein the first average cooling rate is 2 to 50° C. / s within a temperature range from the annealing temperature to a first cooling stop temperature of 350 to 550° C. to cool to the first cooling stop temperature;
[0047] A second cooling step, wherein after staying at a dwell temperature of 350 to 550° C. for 10 seconds or more and 60 seconds or less, the material is cooled to a second cooling stop temperature of 100 to 300° C. at a second average cooling rate of 3 to 50° C. / s;
[0048] a reheating step, wherein heating is performed from the second cooling stop temperature to a reheating temperature of the second cooling stop temperature+50°C or higher and 340°C or lower at an average heating rate of 2.0°C / s or higher; and
[0049] A third cooling step is performed, after the reheating step, by cooling at a third average cooling rate of 0.05 to 1.0° C. / s while staying in a temperature range from the reheating temperature to 50° C. for more than 100 seconds.
[0050] [8] The method for manufacturing a steel sheet according to [7], wherein in the second cooling step, the surface of the steel sheet is subjected to hot-dip galvanizing or alloyed hot-dip galvanizing while the steel sheet is held at a holding temperature of 350 to 550° C. for 10 seconds or more and 60 seconds or less.
[0051] [9] The method for manufacturing a steel sheet according to [7], wherein after the annealing, the surface of the steel sheet is subjected to electrogalvanizing.
[0052]
[10] A method for manufacturing a component, comprising the step of subjecting the steel plate according to any one of [1] to [5] to at least one of a forming process and a joining process to produce the component.
[0053] Effects of the Invention
[0054] According to the present invention, a steel sheet having a high strength with a tensile strength TS of 980 MPa or more, excellent press formability, ductility and stretch flange formability, and excellent material stability in the sheet width direction can be obtained.
[0055] The steel sheet of the present invention can be applied to, for example, automobile structural members of complex shapes, thereby achieving weight reduction of automobile bodies, and can also reduce environmental load by improving the yield during manufacturing. DETAILED DESCRIPTION
[0056] The present invention will be described in detail below. However, the present invention is not limited to the following embodiments.
[0057] The steel sheet of the present invention has a composition containing, by mass%, C: 0.05-0.20%, Si: 0.40-1.50%, Mn: 1.9-3.5%, P: 0.02% or less, S: 0.01% or less, sol.Al: 0.005-0.50%, N: less than 0.015%, the balance being iron and inevitable impurities, and an area ratio of polygonal ferrite of 10% or more and 57% or less, and a total of upper bainite, tempered martensite and lower bainite. The area ratio is 40% or more and 80% or less, the volume ratio of retained austenite is 3% or more and 15% or less, the area ratio of quenched martensite is 12% or less (including 0%), and the steel structure composed of the remaining structure, with respect to the total area ratio of quenched martensite and retained austenite, the total area ratio of quenched martensite with an aspect ratio of 3 or less and an equivalent circle diameter of 1.6 μm or more and retained austenite is 20% or less, and with respect to the total area ratio of the whole structure, a C-rich region (S C≥0.5 ) is less than 15% in area.
[0058] The steel sheet of the present invention is described below in the order of component composition and steel structure. First, the reasons for limiting the component composition of the present invention are described. It should be noted that in the following description, unless otherwise specified, the % representing the components of the steel are all mass %.
[0059] <C:0.05~0.20%>
[0060] C is contained from the viewpoint of ensuring a predetermined strength by transformation strengthening and from the viewpoint of improving ductility by ensuring a predetermined amount of retained austenite (retained γ). If the C content is less than 0.05%, these effects cannot be sufficiently ensured.
[0061] On the other hand, when the C content exceeds 0.20%, the martensitic transformation start temperature (Ms point) decreases. As a result, in the third cooling step of cooling at a third average cooling rate of 0.05 to 1.0°C / s in the temperature range from the reheating temperature to 50°C, the martensitic transformation and subsequent tempering of the martensite cannot be sufficiently performed. As a result, the quenched martensite and the 0.5 mass% or more C-rich region (S C≥0.5 ) is promoted, and the stretch flange formability and material stability in the plate width direction are reduced.
[0062] Therefore, the C content is set to 0.05% or more and 0.20% or less. The C content is preferably set to 0.08% or more. In addition, the C content is preferably set to 0.18% or less.
[0063] <Si: 0.40~1.50%>
[0064] Si is contained from the viewpoint of strengthening ferrite to increase strength and from the viewpoint of suppressing carbide formation in martensite and bainite and ensuring a predetermined amount of retained γ to improve ductility. When the Si content is less than 0.40%, these effects cannot be sufficiently ensured.
[0065] On the other hand, when the Si content exceeds 1.50%, carbon distribution to the untransformed austenite is excessively promoted, and the C-rich region (S C≥0.5 ) is promoted, and the stretch flange formability and material stability in the plate width direction are reduced. Therefore, the Si content is set to be greater than 0.40% and less than 1.50%. The Si content is preferably greater than 0.60%. In addition, the Si content is preferably set to be less than 1.20%.
[0066] <Mn: 1.9~3.5%>
[0067] Mn is contained from the viewpoint of improving the hardenability of the steel sheet, suppressing the excessive phase transformation of ferrite, promoting the high strength brought about by phase transformation strengthening, and suppressing the formation of carbides in bainite like Si, further promoting the formation of retained austenite that contributes to ductility, thereby further improving ductility. In order to obtain these effects, the Mn content needs to be 1.9% or more.
[0068] On the other hand, when the Mn content exceeds 3.5%, the bainite transformation is significantly delayed, and a predetermined amount of retained austenite cannot be ensured, resulting in a decrease in ductility.
[0069] On the other hand, when the Mn content exceeds 3.5%, it becomes difficult to suppress the formation of coarse quenched martensite, and the stretch flange formability also deteriorates.
[0070] Therefore, the Mn content is set to 1.9% or more and 3.5% or less. The Mn content is preferably 2.1% or more. In addition, the Mn content is preferably 3.3% or less, and more preferably 3.0% or less.
[0071] <P: 0.02% or less>
[0072] P is an element that strengthens steel, but when its content is high, the spot weldability deteriorates. Therefore, the P content is set to 0.02% or less, preferably 0.01% or less. It should be noted that P may not be contained, but it costs a lot to reduce it to less than 0.001%, so the P content is preferably 0.001% or more. The P content is more preferably 0.002% or more, and further preferably 0.005% or more.
[0073] <S: 0.01% or less>
[0074] S is an element that has the effect of improving the oxide scale peeling property during hot rolling and the effect of suppressing nitridation during annealing, but has adverse effects on spot weldability, bendability, and hole expansion. In order to reduce these adverse effects, the S content is set to at least 0.01% or less, preferably 0.0020% or less.
[0075] It should be noted that S may not be contained, but it costs a lot to reduce the S content to less than 0.0001%, so from the viewpoint of manufacturing cost, the S content is preferably 0.0001% or more, more preferably 0.0005% or more, and even more preferably 0.0015% or more.
[0076] <sol.Al:0.005~0.50%>
[0077] Al is contained for the purpose of deoxidation or obtaining retained γ. In order to stably perform deoxidation, the sol.Al content is set to 0.005% or more. The sol.Al content is preferably 0.01% or more.
[0078] On the other hand, when the sol.Al content exceeds 0.50%, Al-based coarse inclusions increase in number, and stretch flange formability decreases. Therefore, the sol.Al content is set to 0.50% or less.
[0079] <N: less than 0.015%>
[0080] N is an element that forms nitrides such as BN, AlN, and TiN in steel, and its content needs to be limited because it reduces stretch flange formability. Therefore, the N content is set to less than 0.015%.
[0081] It should be noted that N may not be contained, but it costs a lot to reduce the N content to less than 0.0001%, so from the viewpoint of manufacturing cost, the N content is preferably 0.0001% or more, more preferably 0.0005% or more, and even more preferably 0.0015% or more.
[0082] The steel sheet composition of the present invention contains the above-mentioned component elements as basic components, and the balance contains iron (Fe) and inevitable impurities. It should be noted that the steel sheet composition of the present invention preferably has a composition consisting of the balance of Fe and inevitable impurities.
[0083] The component composition of the steel sheet of the present invention may appropriately contain one or two or more selected from the following (A) to (C) as optional elements in addition to the above components.
[0084] (A) one or two selected from Ti: 0.1% or less, B: 0.01% or less;
[0085] (B) one or more selected from the group consisting of Cu: 1% or less, Ni: 1% or less, Cr: 1% or less, Mo: 0.5% or less, V: 0.5% or less, and Nb: 0.1% or less;
[0086] (C) One or more selected from the group consisting of Mg: 0.0050% or less, Ca: 0.0050% or less, Sn: 0.1% or less, Sb: 0.1% or less, and REM: 0.0050% or less.
[0087] <Ti: 0.1% or less>
[0088] Ti has the effect of fixing N in the steel in the form of TiN, producing the effect of improving hot ductility and the effect of improving the hardenability of B. In addition, it has the effect of making the structure fine by the precipitation of TiC. In order to obtain these effects, it is preferred that the Ti content is set to 0.002% or more. From the viewpoint of fully fixing N, the Ti content is further preferably set to 0.008% or more. The Ti content is more preferably 0.010% or more.
[0089] On the other hand, when the Ti content exceeds 0.1%, the rolling load increases and the ductility decreases due to the increase in precipitation strengthening. Therefore, when Ti is contained, the Ti content is set to 0.1% or less. Preferably, the Ti content is 0.05% or less, and more preferably 0.03% or less.
[0090] <B: 0.01% or less>
[0091] B is an element that improves the hardenability of steel and has the advantage of easily generating tempered martensite and / or bainite of a specified area ratio. Therefore, it is preferred that the B content be set to 0.0005% or more. In addition, the B content is more preferably 0.0010% or more.
[0092] On the other hand, when the B content exceeds 0.01%, not only the effect is saturated, but also the hot ductility is significantly reduced, resulting in surface defects. Therefore, when B is contained, the B content is set to 0.01% or less. Preferably, the B content is 0.005% or less, and more preferably 0.003% or less.
[0093] <Cu: 1% or less>
[0094] Cu improves the corrosion resistance in the use environment of the car. In addition, the corrosion product with Cu covers the surface of the steel plate and inhibits the effect of hydrogen intrusion into the steel plate. Cu is an element mixed in when the waste is used as a raw material. By allowing the mixing of Cu, the recycled materials can be used as raw materials, which can reduce the manufacturing cost. From such a viewpoint, Cu preferably contains more than 0.005%, and from the viewpoint of improving the delayed fracture resistance, Cu more preferably contains more than 0.05%. More preferably, it is more than 0.10%. However, when the Cu content becomes too much, it leads to the generation of surface defects. Therefore, when Cu is contained, the Cu content is set to less than 1%.
[0095] <Ni: less than 1%>
[0096] Ni is also an element that has the effect of improving corrosion resistance like Cu. In addition, Ni has the effect of suppressing the generation of surface defects that are easily generated when Cu is contained. Therefore, Ni preferably contains more than 0.01%. The Ni content is more preferably more than 0.04%, and further preferably more than 0.06%.
[0097] However, when the Ni content becomes too much, the scale formation in the heating furnace becomes uneven, which becomes the cause of surface defects. In addition, it also leads to increased costs. Therefore, when Ni is contained, the Ni content is set to 1% or less. Preferably, the Ni content is 0.5% or less, and more preferably 0.3% or less.
[0098] <Cr: less than 1%>
[0099] Cr may be contained from the viewpoint of improving the hardenability of steel and inhibiting the formation of carbides in martensite and upper bainite / lower bainite. In order to obtain such effects, the Cr content is preferably set to 0.01% or more. The Cr content is more preferably 0.03% or more, and further preferably 0.06% or more.
[0100] However, if Cr is contained excessively, pitting corrosion resistance deteriorates. Therefore, when Cr is contained, the Cr content is made 1% or less.
[0101] <Mo: 0.5% or less>
[0102] Mo may be contained from the viewpoint of improving the hardenability of steel and inhibiting the formation of carbides in martensite and upper bainite / lower bainite. In order to obtain such effects, the Mo content is preferably 0.01% or more. More preferably, it is 0.03% or more, and further preferably, it is 0.06% or more. More preferably, the Mo content is 0.1% or more, and further more preferably, it is 0.2% or more.
[0103] However, Mo significantly deteriorates the chemical conversion treatability of the cold-rolled steel sheet, and therefore, when Mo is contained, the Mo content is made 0.5% or less.
[0104] <V: 0.5% or less>
[0105] V may be contained from the perspective of improving the hardenability of steel, inhibiting the formation of carbides in martensite, upper bainite / lower bainite, refining the structure, and improving the delayed fracture resistance by precipitating carbides. In order to obtain these effects, the V content is preferably set to 0.003% or more. The V content is more preferably 0.05% or more, and further preferably 0.015% or more. The V content is further preferably 0.02% or more, and further preferably 0.05% or more. The V content is preferably 0.15% or more, and more preferably 0.25% or more.
[0106] However, when V is contained in a large amount, castability is significantly deteriorated, so when V is contained, the V content is set to 0.5% or less. The V content is preferably 0.4% or less, and more preferably 0.3% or less.
[0107] <Nb: 0.1% or less>
[0108] Nb may be contained from the viewpoint of the effect of making the steel microstructure fine and high-strength, the effect of promoting bainite transformation by grain refinement, the effect of improving bendability, and the effect of improving delayed fracture resistance. In order to obtain these effects, the Nb content is preferably set to 0.002% or more. The Nb content is more preferably 0.004% or more, and further preferably 0.010% or more.
[0109] However, when a large amount of Nb is contained, precipitation strengthening becomes too strong and ductility decreases. In addition, it leads to an increase in rolling load and deterioration of castability. Therefore, when Nb is contained, the Nb content is set to less than 0.1%. Preferably, the Nb content is less than 0.07%, more preferably less than 0.05%.
[0110] <Mg: 0.0050% or less>
[0111] Mg fixes O in the form of MgO, and contributes to the improvement of formability such as bendability. Therefore, the Mg content is preferably set to 0.0002% or more. The Mg content is more preferably 0.0004% or more, and further preferably 0.0006% or more.
[0112] On the other hand, when a large amount of Mg is added, the surface quality and bendability deteriorate, so when Mg is contained, the Mg content is set to 0.0050% or less. Preferably, the Mg content is 0.0030% or less.
[0113] <Ca: 0.0050% or less>
[0114] Ca fixes S in the form of CaS, which contributes to the improvement of bendability and delayed fracture resistance. Therefore, the Ca content is preferably set to 0.0002% or more. The Ca content is more preferably 0.0005% or more, and further preferably 0.0010% or more. On the other hand, when a large amount of Ca is added, the surface quality and bendability are deteriorated. Therefore, when Ca is contained, the Ca content is set to 0.0050% or less. Preferably, the Ca content is 0.0040% or less.
[0115] <Sn: 0.1% or less>
[0116] Sn inhibits oxidation and nitridation of the surface layer of the steel plate, and inhibits the reduction of the content of C and B in the surface layer caused by this. Through this effect, the ferrite formation of the surface layer of the steel plate is inhibited, high strength is achieved, and fatigue resistance is improved. From this point of view, the Sn content is preferably set to 0.002% or more. The Sn content is more preferably 0.004% or more, and further preferably 0.006% or more. More preferably, the Sn content is 0.01% or more, and further more preferably 0.05% or more.
[0117] On the other hand, when the Sn content exceeds 0.1%, castability deteriorates. In addition, Sn segregates at the original γ grain boundary, and delayed fracture resistance deteriorates. Therefore, when Sn is contained, the Sn content is set to 0.1% or less.
[0118] <Sb: 0.1% or less>
[0119] Sb inhibits oxidation and nitridation of the surface layer of the steel plate, and inhibits the reduction of the content of C and B in the surface layer caused by this. Through this effect, the ferrite formation of the surface layer of the steel plate is inhibited, high strength is achieved, and fatigue resistance is improved. From this point of view, the Sb content is preferably set to 0.002% or more. The Sb content is more preferably 0.004% or more, and further preferably 0.006% or more. The Sb content is more preferably 0.01% or more, and further more preferably 0.05% or more.
[0120] On the other hand, when the Sb content exceeds 0.1%, the castability is deteriorated, and further, the Sb segregates at the original γ grain boundary, and the delayed fracture resistance is deteriorated. Therefore, when Sb is contained, the Sb content is set to 0.1% or less.
[0121] <REM: 0.0050% or less>
[0122] REM is an element that suppresses the adverse effects of sulfides on stretch flange formability by spheroidizing the shape of sulfides, thereby improving stretch flange formability. In order to obtain these effects, the REM content is preferably set to 0.0005% or more. The REM content is more preferably 0.0010% or more, and further preferably 0.0020% or more.
[0123] On the other hand, when the REM content exceeds 0.0050%, the effect of improving the stretch flange formability is saturated. Therefore, when REM is contained, the REM content is made 0.0050% or less.
[0124] It should be noted that the REM mentioned in the present invention refers to the lanthanide elements of scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM concentration in the present invention refers to the total content of one or more elements selected from the above REM.
[0125] When the optional components are contained in an amount less than the lower limit, the optional elements contained in an amount less than the lower limit do not impair the effects of the present invention. Therefore, when the optional elements are contained in an amount less than the lower limit, the optional elements are contained as unavoidable impurities.
[0126] Next, the mechanical properties of the steel sheet (cold-rolled steel sheet having excellent material stability) to which the present invention is applied will be described.
[0127] The tensile strength (TS) of the steel sheet of the present invention is set to 980 MPa or more. The upper limit of the tensile strength is not particularly limited, but from the viewpoint of taking other characteristics into consideration, the tensile strength is preferably 1300 MPa or less.
[0128] The steel sheet of the present invention ensures a total elongation EL of 14.0% or more when TS is 980 MPa or more and a total elongation EL of 12.0% or more when TS is 1180 MPa or more, thereby significantly improving the stability of press forming.
[0129] By ensuring a hole expansion ratio λ of 40% or more, cracks during press forming can be suppressed, and the system can also be applied to difficult-to-form complex formed parts. Therefore, λ is set to 40% or more.
[0130] In the steel plate of the present invention, the plate width of region A that continuously satisfies the following equations (1) and (2) regarding EL and λ at the measurement position X in the plate width direction is 80% or more of the total plate width.
[0131] -10≤100×[(EL(%) at measurement position X in area A - EL(%) at center of board width) / EL(%) at center of board width]≤10 …(1)
[0132] -10≤100×[(λ(%) at measurement position X in region A - λ(%) at center of plate width) / λ(%) at center of plate width]≤10 …(2)
[0133] In formulas (1) and (2), the measurement position X is set to a total of 23 locations of the 24 division positions of the plate width W of the steel plate (the contact locations of the adjacent widths of the 23 locations when the plate width W is divided into 24 equal widths). That is, as the positions in the plate width direction, W / 24, 2W / 24, 3W / 24, 4W / 24, 5W / 24, 6W / 24, 7W / 24, 8W / 24, 9W / 24, 10W / 24, 11W / 24, 12W / 24, 13W / 24, 14W / 24, 15W / 24, 16W / 24, 17W / 24, 18W / 24, 19W / 24, 20W / 24, 21W / 24, 22W / 24, and 23W / 24, a total of 23 locations are set as the measurement position X.
[0134] Here, for example, when the measurement position X that continuously satisfies equations (1) and (2) is 2W / 24 to 20W / 24, the plate width of region A that continuously satisfies equations (1) and (2) is 100×(20-2+1) / 23=83% of the total plate width.
[0135] In the steel plate of the present invention, the region A has a length in the plate width direction that is 80% or more of the total plate width.
[0136] That is, for the steel plate of the present invention, the area where the deviation of EL in the plate width direction is 10% or less relative to the measured value at the center of the plate width and the deviation of λ in the plate width direction is 10% or less relative to the measured value at the center of the plate width is set to 80% or more relative to the total plate width area. The range of the unstable portion is allowed to be up to 20% in total at both ends in the width direction.
[0137] The end of the steel plate contacts other structures during the transportation and operation of the steel plate, so the end is not used for the purpose of ensuring quality. Therefore, the usable effective plate width does not reach 100%. Therefore, the effective plate width is preferably set to less than 100%.
[0138] By making the deviation of EL in the board width direction less than 10% of the measured value at the center of the board width and the area where the deviation of λ is less than 10% relative to the total board width more than 80%, the yield rate can be significantly improved. Therefore, in the present invention, the deviation of EL in the board width direction less than 10% of the measured value at the center of the board width and the area where the deviation of λ is less than 10% relative to the total board width is set to more than 80%, preferably more than 85%.
[0139] <YR≤0.8、TS≥980MPa、EL≥14.0%>
[0140] <YR≤0.8、TS≥1180MPa、EL≥12.0%>
[0141] In the evaluation of tensile properties, a JIS No. 5 tensile test piece is cut from the center of the plate width, and a tensile test is performed with N=3 (according to JIS Z2241 (2011)). Each evaluation is based on the average value of 3 points. Steel plates with a tensile strength of 980 MPa or more are regarded as high-strength steel plates. Steel plates with a yield ratio YR of 0.8 or less are regarded as steel plates with excellent stamping formability. Steel plates with a total elongation EL of 14.0% or more when TS is 980 MPa or more and a total elongation EL of 12.0% or more when TS is 1180 MPa or more are regarded as steel plates with excellent ductility.
[0142] <λ≥40%>
[0143] In the evaluation of the stretch flange formability, a test piece is cut from the center of the plate width, and a hole expansion test is performed with N=3 according to the provisions of the Japan Iron and Steel Federation Standard JFST1001. That is, after a punching tool with a punch diameter of 10mm and a gap of 13% is used to punch a sample of 100mm×100mm square size, a conical punch with a vertex angle of 60 degrees is used to expand the hole with the burr generated when the punching hole is formed on the outside until a crack that penetrates the plate thickness is generated. Based on d0: initial hole diameter (mm) and d: hole diameter when cracks occur (mm) at this time, the hole expansion rate λ(%)={(d-d0) / d0}×100 is calculated, and the average value of the three points obtained is evaluated as λ. Steel with a λ of 40% or more is judged to have excellent hole expansion and excellent stretch flangeability.
[0144] <Evaluation of material stability in the board width direction>
[0145] As an evaluation of the material stability in the board width direction, 23 points (including the board width center position) of the evaluation material were cut from the board width center position (the above-mentioned 12W / 24 position) at intervals of less than 100 mm from both board width directions, and the EL and λ at each position (measurement position X) were calculated. Then, the ratio of the difference between the measured value at the board width center position and each position to the measured value at the board width center position was calculated to evaluate the material stability in the board width direction.
[0146] Taking EL and λ at the center of the plate width as the reference, the continuous measurement group in which the difference between EL and λ is less than 10% is regarded as the area in which the difference between EL and λ is less than 10%, and the steel having the ratio of this area to the total plate width being 80% or more is judged as having excellent material stability.
[0147] It should be noted that the plate width of the steel plate in the present invention is preferably 600 mm or more. In addition, the plate width of the steel plate in the present invention is preferably 1700 mm or less.
[0148] Next, the steel structure of the steel plate of the present invention will be described.
[0149] <Area ratio of polygonal ferrite: 10% or more and 57% or less>
[0150] From the viewpoint of low YR and ensuring high ductility, the area ratio of polygonal ferrite is set to 10% or more, and in order to obtain higher ductility, it is preferably set to 20% or more.
[0151] On the other hand, if the polygonal ferrite exceeds 57%, the predetermined strength cannot be obtained, so the area ratio of polygonal ferrite is set to 57% or less, preferably 55% or less, and more preferably 50% or less.
[0152] <Total area ratio of upper bainite, tempered martensite, and lower bainite: 40% or more and 80% or less>
[0153] In order to obtain desired strength, the total area ratio of upper bainite, tempered martensite, and lower bainite is set to 40% or more, and in order to obtain higher strength, it is preferably set to 45% or more.
[0154] However, when the total area ratio of upper bainite, tempered martensite, and lower bainite exceeds 80%, ductility decreases due to excessively high strength, so the area ratio is set to 80% or less, and more preferably set to 75% or less.
[0155] <Volume ratio of retained austenite (retained γ): 3% or more and 15% or less>
[0156] In order to ensure the desired ductility, it is effective to set the volume fraction of retained austenite to 3% or more. Therefore, the volume fraction of retained austenite is set to 3% or more, preferably 5% or more.
[0157] On the other hand, if the retained austenite exceeds 15%, stretch flange formability decreases, so the retained austenite is set to 15% or less, more preferably 13% or less.
[0158] <Quenched martensite: 12% or less (including 0%)>
[0159] The hard quenched martensite structure reduces λ, so its area ratio needs to be suppressed. In order to obtain the desired λ, the area ratio of quenched martensite is set to 12% or less. In order to obtain λ more stably, the area ratio of quenched martensite is preferably 10% or less.
[0160] <Remaining Organization>
[0161] Regarding the steel structure, the rest of the above is composed of the remaining structure. The area ratio of the remaining structure is preferably set to 5% or less. The remaining structure can be carbide or pearlite. These structures can be determined by SEM observation as described later.
[0162] <Total area ratio of quenched martensite and retained austenite with an aspect ratio of 3 or less and an equivalent circle diameter of 1.6 μm or more relative to the total area ratio of quenched martensite and retained austenite: 20% or less>
[0163] The retained austenite becomes a hard martensite structure by the TRIP effect in stamping, drawing, etc. Therefore, in the present invention, from the viewpoint of stretch flangeability, the quenched martensite and the retained austenite are controlled together. If the quenched martensite or retained austenite with an equivalent circle diameter of 1.6 μm or more is formed, voids may be formed in the stress concentration portion of the interface with other structures, and the desired stretch flange formability cannot be obtained.
[0164] In addition, when the aspect ratio of the quenched martensite or retained austenite is 3 or less, stress concentration is likely to occur at the interface with other structures, thereby promoting void formation and deteriorating the stretch flange formability. Therefore, the total area ratio of the quenched martensite and retained austenite with an aspect ratio of 3 or less and an equivalent circle diameter of 1.6 μm or more is set to 20% or less relative to the total area ratio of the quenched martensite and retained austenite. It is preferably set to 18% or less.
[0165] The lower limit of the total area ratio of quenched martensite and retained austenite having an aspect ratio of 3 or less and an equivalent circle diameter of 2.0 μm or more relative to the total area ratio of quenched martensite and retained austenite is not particularly set, but it is difficult to control to 0% from the viewpoint of operability, so it is preferably set to 2% or more, and more preferably set to 4% or more.
[0166] The equivalent circle diameter is preferably 20.0 μm or less.
[0167] <C-rich region with a C concentration of 0.5 mass % or more relative to the total tissue (S C≥0.5 ) Area ratio: 15% or less>
[0168] The hardness of quenched martensite is determined by the amount of C dissolved in the quenched martensite. If the hardness difference between quenched martensite and other tissues increases, the formation of voids is promoted at the interface of the stress concentration part. The tissues containing a large amount of dissolved C are quenched martensite and retained austenite. Retained austenite is a tissue that contributes to high ductility. When the C concentration is 0.5 mass% or more and the area ratio of the tissue with a C concentration of 0.5 mass% or more is 15% or less relative to the total constituent tissue, it is possible to improve ductility while ensuring stretch flange formability, and it is also possible to reduce material fluctuations in the plate width direction, and it is possible to manufacture steel plates with excellent material stability. Therefore, the C-rich region (S C≥0.5 ) is set to a duty factor of less than 15%.
[0169] It is preferably 12% or less, and more preferably 10% or less.
[0170] In addition, it is preferably 6% or more, and more preferably 8% or more.
[0171] Next, the method of measuring the steel structure will be described.
[0172] The area ratios of polygonal ferrite, upper bainite, tempered martensite, lower bainite, and quenched martensite (fresh martensite) are determined as follows: a section of the plate thickness parallel to the rolling direction is cut out, mirror polished, and then corroded with a 1 volume % nitric acid ethanol solution. Ten fields of view are observed at 5000 times using a SEM at the 1 / 4 thickness position, and the photographs of the structure taken are quantified using image analysis.
[0173] Polygonal ferrite contains almost no carbides and is relatively equiaxed ferrite. It is the darkest region in SEM.
[0174] Upper bainite is a ferrite structure with carbides or residual austenite that appear white in SEM. It should be noted that when it is difficult to distinguish between upper bainite and polygonal ferrite, the area of ferrite with an aspect ratio of ≤2.0 is classified as polygonal ferrite, and the area of aspect ratio>2.0 is classified as upper bainite, and the area ratio is calculated. Here, with respect to the aspect ratio, the longest major axis length a of the particle is calculated, and the particle length when the particle is longest in the direction perpendicular to it is set as the minor axis length b, and a / b is taken as the aspect ratio.
[0175] Tempered martensite and lower bainite are regions that are accompanied by lath-shaped lower structures and precipitation of carbides in the interior in SEM.
[0176] The quenched martensite (fresh martensite) is a block-like region that appears whitish with no underlying structure visible in the SEM.
[0177] The remaining structure is carbide and / or pearlite structure, which can be confirmed by white contrast in SEM. Carbide is a structure with a grain size of 1 μm or less, and pearlite is a lamellar (layered) structure, so it can be distinguished.
[0178] The quantitative evaluation of the above-mentioned structure and the measurement of the aspect ratio and equivalent circle diameter of the quenched martensite and retained austenite can be performed using image analysis software, for example, Image J (Fiji).
[0179] A plate thickness section parallel to the rolling direction can be cut out, mirror polished, and then etched with a 1% by volume nitric acid solution. Ten fields of view are observed at 5000 times with SEM at the 1 / 4 thickness position, and each structure is identified and quantitatively evaluated using the Trainable Weka segmentation method that can perform region identification through machine learning in Image J (Fiji). In addition, the aspect ratio and equivalent circle diameter of quenched martensite and retained austenite can be measured by a particle analysis program that is also a function of Image J, and only the quenched martensite and retained austenite identified as described above are extracted for measurement.
[0180] The volume fraction of retained austenite was determined by chemically polishing the surface layer to a 1 / 4 thickness position and then by X-ray diffraction. A Co-Kα ray source was used as the incident X-ray, and the volume fraction of retained austenite was calculated from the intensity ratio of the (200), (211), and (220) planes of ferrite to the (200), (220), and (311) planes of austenite. Since the retained austenite is randomly distributed, the volume fraction of retained austenite determined by X-ray diffraction can be used as the area fraction of retained austenite.
[0181] The area ratio S of the C-rich region where the C concentration is 0.5 mass % or more C≥0.5 In the measurement, a field emission electron probe microanalyzer (FE-EPMA) JXA-8500F manufactured by JEOL Ltd. was used at the 1 / 4 position of the plate thickness of the plate thickness section parallel to the rolling direction. Then, the acceleration voltage was 6 kV and the irradiation current was 7 × 10 -8 A. The beam diameter is the smallest, and the C concentration distribution is measured by mapping analysis to calculate the area ratio of the C concentration of 0.5 mass % or more.
[0182] However, in order to eliminate the influence of contamination, the background portion is subtracted so that the average value of C obtained by analysis is equal to the carbon amount of the base material. That is, when the average value of the measured carbon amount is greater than the carbon amount of the base material, the increase is considered to be contamination, and the value obtained by subtracting the increase from the analysis value at each position is taken as the true C amount at each position.
[0183] Next, the method for producing the steel sheet of the present invention will be described.
[0184] The method for manufacturing a steel plate of the present invention is a method for manufacturing a steel plate by hot rolling, pickling and cold rolling a steel billet having a component composition, and then annealing the obtained cold-rolled steel plate, wherein the annealing comprises: a holding step, wherein the cold-rolled steel plate is heated to an annealing temperature of 750 to 880° C. and maintained at the annealing temperature for 10 to 500 seconds; a first cooling step, wherein the cold-rolled steel plate is cooled to the first cooling stop temperature at a first average cooling rate of 2 to 50° C. / s within a temperature range from the annealing temperature to a first cooling stop temperature of 350 to 550° C.; a second cooling step, wherein the cold-rolled steel plate is cooled to the first cooling stop temperature at a first average cooling rate of 2 to 50° C. / s within a temperature range from the annealing temperature to a first cooling stop temperature of 350 to 550° C.; and a second cooling step, wherein the cold-rolled steel plate is cooled to the first cooling stop temperature at a first average cooling rate of 2 to 50° C. / s within a temperature range from the annealing temperature to a first cooling stop temperature of 350 to 550° C. After staying at a dwell temperature of 550°C for more than 10 seconds and less than 60 seconds, cooling to a second cooling stop temperature of 100 to 300°C at a second average cooling rate of 3 to 50°C / s; a reheating process, wherein heating is performed from the above-mentioned second cooling stop temperature to a reheating temperature of more than the second cooling stop temperature + 50°C and less than 340°C at an average heating rate of more than 2.0°C / s; and a third cooling process, wherein, after the above-mentioned reheating process, cooling is performed at a third average cooling rate of 0.05 to 1.0°C / s while staying in a temperature range from the above-mentioned reheating temperature to 50°C for more than 100 seconds.
[0185] <Hot rolling>
[0186] The methods for hot rolling a steel billet include a method of rolling the steel billet after heating it, a method of directly rolling the steel billet after continuous casting without heating it, a method of heating the steel billet after continuous casting for a short time and then rolling it, etc. Hot rolling can be carried out according to conventional methods. For example, the steel billet heating temperature is set to 1100-1300°C, the soaking temperature is set to 20-300 minutes, the finishing rolling temperature is set to Ar3 transformation point ~ Ar3 transformation point + 200°C, and the coiling temperature is set to 400-720°C. From the viewpoint of suppressing the variation of the plate thickness and stably ensuring high strength, the coiling temperature is preferably set to 430-530°C.
[0187] The Ar3 transformation point can be calculated based on the composition of the steel sheet and the following empirical formula (A).
[0188] Ar3=910-203×[C]+44.7×[Mn]-30×[Si]+700×[P]+400×[sol.Al]-20×[B]+31.5×[Mo]+104×[V]+400×[Ti]…(A)
[0189] In formula (A), "element" refers to the content (mass %) of each element. (Elements not contained are set to 0 (zero) mass %).
[0190] <Pickling>
[0191] Pickling can be carried out according to conventional methods.
[0192] <Cold rolling>
[0193] Cold rolling can be carried out according to conventional methods, and the cumulative rolling rate can be set to 30-85%. From the viewpoint of stably ensuring high strength and reducing anisotropy, the rolling rate is preferably set to 35-85%. It should be noted that, when the rolling load is high, a softening annealing treatment can be performed at 450-730°C using CAL (continuous annealing line) or BAF (box annealing furnace).
[0194] <Annealing>
[0195] The cold rolled steel sheet (cold rolled steel sheet) manufactured by a conventional method is annealed under the following conditions. The annealing equipment is not particularly limited, but from the viewpoint of ensuring productivity and desired heating and cooling rates, it is preferably carried out by a continuous annealing line (CAL) or a continuous hot-dip galvanizing line (CGL).
[0196] [Holding step: heating to an annealing temperature in the annealing temperature range of 750 to 880° C., and holding at the annealing temperature for 10 to 500 seconds]
[0197] When the annealing temperature (soaking temperature) is lower than 750°C, polygonal ferrite becomes excessive, thereby increasing C and Mn enriched in the reverse transformation austenite. As a result, at least any one of upper bainite, tempered martensite, lower bainite, and retained austenite cannot be sufficiently obtained, and the hardness of quenched martensite increases, thereby failing to ensure the desired strength, ductility, and stretch flange formability. In addition, when the annealing temperature (soaking temperature) is lower than 750°C, recrystallization sometimes does not occur sufficiently, and the processed structure during cold rolling remains, thereby reducing the formability. Therefore, the annealing temperature (soaking temperature) is set to 750°C or more.
[0198] On the other hand, when the annealing temperature (soaking temperature) exceeds 880°C, it becomes an austenite single phase temperature, the specified polygonal ferrite cannot be obtained, YR increases and ductility decreases. Therefore, the annealing temperature (soaking temperature) is set to 880°C or less. The annealing temperature (soaking temperature) is preferably 850°C or less, and more preferably 830°C or less.
[0199] In addition, when the time held at the above-mentioned annealing temperature (soaking time) is less than 10 seconds, the formation of austenite at the above-mentioned annealing temperature (soaking temperature) does not proceed sufficiently, polygonal ferrite becomes excessive, the specified amount of upper bainite, tempered martensite, and lower bainite cannot be obtained, and the desired strength cannot be obtained. Not only that, retained austenite cannot be sufficiently obtained, and the desired ductility cannot be ensured.
[0200] On the other hand, when the holding time (soaking time) at the annealing temperature exceeds 500 seconds, the structure becomes coarsened significantly, and thus the desired strength cannot be ensured.
[0201] Therefore, the time (soaking time) held at the above annealing temperature is set to 10 to 500 seconds. The time (soaking time) held at the annealing temperature is preferably 80 seconds or more, more preferably 100 seconds or more. In addition, the time (soaking time) held at the annealing temperature is preferably 400 seconds or less, more preferably 300 seconds or less.
[0202] [First cooling step: cooling to the first cooling stop temperature at a first average cooling rate of 2 to 50°C / s within a temperature range from the annealing temperature to the first cooling stop temperature of 350 to 550°C]
[0203] After holding at a soaking temperature of 750°C to 880°C (after the above-mentioned holding step), cooling is performed at a first average cooling rate of 2 to 50°C / s in a temperature range from the above-mentioned annealing temperature to a first cooling stop temperature of 350 to 550°C. When the cooling rate is less than 2°C / s, the workability is reduced, so the first average cooling rate is set to 2°C / s or more. The first average cooling rate is preferably 5°C / s or more.
[0204] On the other hand, if the first average cooling rate becomes too high, the sheet shape deteriorates, so it is set to 50° C. / s or less. The first average cooling rate is preferably 40° C. / s or less, and more preferably less than 30° C. / s.
[0205] Here, the first average cooling rate means "(annealing temperature (° C.)−first cooling stop temperature (° C.)) / cooling time (seconds) from the annealing temperature to the first cooling stop temperature".
[0206] [Second cooling step (1): staying at a stay temperature of 350 to 550° C. for 10 s or more and 60 s or less]
[0207] In the temperature range of 350°C to 550°C (dwelling temperature) below the first cooling stop temperature, upper bainite can be formed, a predetermined retained austenite can be obtained, and the desired ductility can be obtained. Bainite transformation has a latent period, and it is necessary to stay for a certain period of time in the dwelling temperature range including the dwelling start temperature and the dwelling end temperature.
[0208] When the dwell temperature range is lower than 350°C or higher than 550°C, the bainite transformation is suppressed, resulting in the formation of retained austenite being suppressed, and the desired ductility cannot be obtained. In addition, when the dwell temperature range is lower than 350°C, martensitic transformation occurs, so YR is unnecessarily increased, and stamping formability is sometimes reduced. Therefore, the dwell temperature range is set to 350-550°C.
[0209] On the other hand, when the residence time is less than 10 seconds, a desired amount of bainite cannot be obtained, and the formation of retained austenite is suppressed, resulting in that desired ductility cannot be obtained.
[0210] On the other hand, when the residence time exceeds 60 seconds, C is enriched from bainite to massive untransformed γ, resulting in an increase in coarse quenched martensite with a high C concentration, and the desired stretch flange formability and material stability in the plate width direction cannot be obtained. Therefore, the residence time is set to be 10 seconds or more and 60 seconds or less.
[0211] [Second cooling step (2): cooling at a second average cooling rate of 3 to 50°C / s in a temperature range to a second cooling stop temperature of 100 to 300°C]
[0212] After the above-mentioned stay, rapid cooling is required to prevent the decrease in the amount of tempered martensite caused by excessive bainite transformation, the formation of coarse quenched martensite or retained austenite, and the reduction in strength, stretch flange formability and material stability in the plate width direction caused by excessive carbon enrichment in the retained austenite. Therefore, the average cooling rate (second average cooling rate) in the temperature range from the above-mentioned stay end temperature to the cooling stop temperature of 100°C or more and 300°C or less is set to 3°C / s or more. The second average cooling rate is preferably set to 5°C / s.
[0213] On the other hand, if the second average cooling rate exceeds 50° C. / s, the sheet shape deteriorates, so the second average cooling rate is set to 50° C. / s or less.
[0214] When the second cooling stop temperature exceeds 300° C., the predetermined tempered martensite cannot be obtained, resulting in an increase in coarse quenched martensite, and thus the desired stretch flange formability cannot be obtained. Therefore, the second cooling stop temperature is set to 300° C. or less. The second cooling stop temperature is preferably 290° C. or less.
[0215] On the other hand, when the second cooling stop temperature is lower than 100° C., martensitic transformation proceeds excessively, and retained austenite of a predetermined volume fraction cannot be obtained, and desired ductility cannot be obtained. Therefore, the cooling stop temperature is set to 100° C. or higher.
[0216] Here, the second average cooling rate means "stay end temperature (° C.) - second cooling stop temperature (° C.) / cooling time (seconds) from the stay end temperature to the second cooling stop temperature".
[0217] [Reheating step: heating from the second cooling stop temperature to a reheating temperature of the second cooling stop temperature + 50°C to 340°C at an average heating rate of 2.0°C / s or more]
[0218] The tempering effect of martensite is promoted at higher temperatures. Therefore, compared with tempering at the second cooling stop temperature + 50°C or above, by tempering, carbon enrichment is promoted, the formation of retained austenite is promoted, stretch flange formability is improved, and ductility can be improved.
[0219] On the other hand, when the reheating temperature exceeds 340°C, carbide precipitation is promoted, so carbon enrichment is suppressed and the predetermined retained austenite cannot be obtained, and the desired ductility cannot be obtained. Therefore, the reheating temperature is set to be above the cooling stop temperature + 50°C and below 340°C.
[0220] In addition, when the average heating rate is less than 2.0°C / s, carbide precipitation is promoted compared to carbon distribution, resulting in failure to obtain the desired retained austenite. Therefore, the average heating rate in the temperature range from the cooling stop temperature to 340°C or less is set to 2.0°C / s or more.
[0221] Here, the average heating rate means "reheating temperature (° C.) - second cooling stop temperature (° C.) / heating time (seconds) from the second cooling stop temperature to the reheating temperature".
[0222] [Third cooling step: cooling at a third average cooling rate of 0.05 to 1.0°C / s while staying in a temperature range from the reheating temperature to 50°C for 100 seconds or more]
[0223] When the third average cooling rate in the temperature range from the reheating temperature to 50°C exceeds 1.0°C / s, the tempering effect of martensite cannot be sufficiently obtained, and the C-rich region (S C≥0.5 ) increases, thereby deteriorating the stretch flange formability and material stability in the plate width direction. Therefore, the cooling rate in the temperature range from the reheating temperature to 50°C is set to 1.0°C / s or less.
[0224] Note that by setting the cooling rate in the temperature range from the reheating temperature to 50° C. to 1.0° C. / s or less, the temperature fluctuation in the sheet width direction is also reduced, and the material stability in the sheet width direction can be further improved.
[0225] On the other hand, if the cooling rate (third average cooling rate) in the temperature range from the reheating temperature to 50°C is slow, the processing time becomes longer, and the workability is deteriorated. Therefore, the cooling rate (third average cooling rate) in the temperature range from the cooling stop temperature to 50°C is set to 0.05°C / s or more.
[0226] Here, the third average cooling rate means "reheating temperature (° C.)-50° C. / cooling time (seconds) from the reheating temperature (° C.) to 50° C.".
[0227] In addition, the surface of the steel sheet may be subjected to a galvanizing treatment to obtain a steel sheet having a zinc coating on the surface. The type of the coating treatment is not particularly limited, and may be any of hot-dip galvanizing and electro-galvanizing. In addition, as an alloying hot-dip galvanizing treatment, a coating treatment in which alloying is performed after hot-dip galvanizing may be performed.
[0228] Hot-dip galvanizing is used for automobile steel sheets, etc. In the case of hot-dip galvanizing, in a continuous annealing furnace at the front end of a continuous hot-dip galvanizing line, after the holding step and the first cooling step in the annealing, the steel sheet is immersed in a hot-dip galvanizing bath to form a hot-dip galvanized layer on the surface of the steel sheet, and then alloying treatment can be performed to produce an alloyed hot-dip galvanized steel sheet.
[0229] Specifically, in the second cooling step, when the steel sheet is kept at a temperature of 350 to 550° C. for 10 seconds or more and 60 seconds or less, the surface of the steel sheet may be subjected to hot-dip galvanizing or alloy hot-dip galvanizing. In addition, the soaking and cooling steps and the plating step may be performed on different production lines.
[0230] In addition, electrogalvanizing may be performed after annealing, that is, after the third cooling step.
[0231] The thickness of the steel sheet of the present invention obtained as described above is preferably set to 0.5 mm or more. In addition, the thickness of the steel sheet of the present invention is preferably set to 2.0 mm or less.
[0232] In addition, the plate width is preferably set to 600 mm or more. In addition, the plate width of the steel plate of the present invention is preferably set to 1700 mm or less.
[0233] Next, the member of the present invention and a method for producing the same will be described.
[0234] The component of the present invention is a component formed by subjecting the steel plate of the present invention to at least one of forming and joining. In addition, the method for manufacturing the component of the present invention includes the step of subjecting the steel plate of the present invention to at least one of forming and joining to form the component.
[0235] The tensile strength of the steel plate of the present invention is above 980 MPa, and it has excellent stamping formability, ductility and stretch flange formability, and excellent material stability in the plate width direction. Therefore, the component obtained using the steel plate of the present invention is also high-strength, excellent stamping formability, ductility and stretch flange formability, and excellent material stability in the plate width direction. In addition, if the component of the present invention is used, lightweighting can be achieved. Therefore, the component of the present invention can be suitable for use in, for example, vehicle body frame parts. The component of the present invention also includes a welded joint.
[0236] The forming process can use general processing methods such as press working without limitation. In addition, the joining process can use general welding such as spot welding, arc welding, riveting, caulking, etc. without limitation.
[0237] Example
[0238] The steel slabs produced by continuous casting and having the composition shown in Table 1 were heated to 1200°C, and after a hot rolling process with a soaking time of 200 minutes, a finishing rolling temperature of 900°C, and a coiling temperature of 550°C, cold rolling was performed at a rolling ratio of 50%. The cold-rolled steel sheets having a thickness of 1.4 mm produced in this way were treated under the annealing conditions shown in Table 2 to produce the steel sheets of the present invention and the steel sheets of the comparative examples.
[0239] The plate widths of the obtained steel plates were all 1500 mm.
[0240]
[0241] It should be noted that when a portion of the steel sheets (cold-rolled steel sheets: CR) stay at a dwell temperature of 350 to 550°C for more than 10s and less than 60s, hot-dip galvanizing treatment is performed to make hot-dip galvanized steel sheets (GI). Here, the steel sheet is immersed in a galvanizing bath at a temperature of more than 440°C and less than 550°C to perform hot-dip galvanizing treatment, and then the coating adhesion amount is adjusted by gas wiping or the like. Hot-dip galvanizing uses a galvanizing bath with an Al content of more than 0.10% and less than 0.22%. Furthermore, a portion of the hot-dip galvanized steel sheets are alloyed after the above-mentioned hot-dip galvanizing treatment to make alloyed hot-dip galvanized steel sheets (GA). Here, alloying treatment is performed in a temperature range of more than 460°C and less than 550°C. In addition, a portion of the steel sheets (cold-rolled steel sheets: CR) are electroplated to make electrogalvanized steel sheets (EG).
[0242] The steel structure was measured by the following method. The measurement results are shown in Table 3.
[0243] The area ratios of polygonal ferrite, upper bainite, tempered martensite, lower bainite, and quenched martensite (fresh martensite) are determined as follows: a section of the plate thickness parallel to the rolling direction is cut out, mirror polished, and then corroded with a 1 volume % nitric acid ethanol solution. Ten fields of view are observed at 5000 times using a SEM at the 1 / 4 thickness position, and the photographs of the structure taken are quantified using image analysis.
[0244] Polygonal ferrite contains almost no carbides and is relatively equiaxed ferrite. It is the darkest region in SEM.
[0245] Upper bainite is a ferrite structure with carbides or residual austenite that appear white in SEM. It should be noted that when it is difficult to distinguish between upper bainite and polygonal ferrite, the area of ferrite with an aspect ratio of ≤2.0 is classified as polygonal ferrite, and the area with an aspect ratio of >2.0 is classified as upper bainite, and the area ratio is calculated. Here, regarding the aspect ratio, the longest major axis length a of the particle is calculated, and the particle length when it is longest across the particle in the direction perpendicular to it is set as the minor axis length b, and a / b is proportional to the aspect ratio.
[0246] Tempered martensite and lower bainite are regions that are accompanied by lath-shaped lower structures and precipitation of carbides in the interior in SEM.
[0247] The quenched martensite (fresh martensite) is a block-like region that appears whitish with no underlying structure visible in the SEM.
[0248] The remaining structure is carbide and / or pearlite, which can be confirmed as a white contrast in SEM. Carbide is a structure with a grain size of 1 μm or less, and pearlite is a lamellar structure, so it can be distinguished.
[0249] The quantitative evaluation of the above-mentioned structures and the measurement of the aspect ratio and equivalent circle diameter of the quenched martensite and retained austenite were performed using Image J (Fiji) as image analysis software.
[0250] A plate thickness section parallel to the rolling direction can be cut out, mirror polished, and then etched with a 1% by volume nitric acid solution. Ten fields of view are observed at 5000 times with SEM at the 1 / 4 thickness position, and each structure is identified and quantitatively evaluated using the Trainable Weka segmentation method that can perform region identification through machine learning in Image J (Fiji). In addition, the aspect ratio and equivalent circle diameter of quenched martensite and retained austenite can be measured by a particle analysis program that is also a function of Image J, and only the quenched martensite and retained austenite identified as described above are extracted for measurement.
[0251] The volume fraction of retained austenite was determined by chemically polishing the surface layer to a position of 1 / 4 thickness and then performing X-ray diffraction. A Co-Kα source was used as the incident X-ray source, and the volume fraction of retained austenite was calculated from the intensity ratio of the (200), (211), and (220) planes of ferrite to the (200), (220), and (311) planes of austenite.
[0252] The area ratio S of the C-rich region where the C concentration is 0.5 mass % or more C≥0.5In the measurement, a field emission electron probe microanalyzer (FE-EPMA) JXA-8500F manufactured by JEOL Ltd. was used at the 1 / 4 position of the plate thickness of the plate thickness section parallel to the rolling direction. Then, the acceleration voltage was 6 kV and the irradiation current was 7 × 10 -8 A. The beam diameter is the smallest, and the C concentration distribution is measured by mapping analysis to calculate the area ratio of the C concentration of 0.5 mass % or more.
[0253] However, in order to eliminate the influence of contamination, the background portion is subtracted so that the average value of C obtained by analysis is equal to the carbon amount of the base material. That is, when the average value of the measured carbon amount is greater than the carbon amount of the base material, the increase is considered to be contamination, and the value obtained by subtracting the increase from the analysis value at each position is taken as the true C amount at each position.
[0254] In the evaluation of tensile properties, a JIS No. 5 tensile test piece is cut from the center of the plate width, and a tensile test is performed with N=3 (according to JIS Z2241 (2011)). For each evaluation, it is performed based on the average value of 3 points. Steel plates with a tensile strength of 980 MPa or more are judged to have excellent strength. Steel plates with a yield ratio YR of 0.8 or less are judged to have excellent stamping formability. When the total elongation EL is 14.0% or more when TS is 980 MPa or more, and when the total elongation EL is 12.0% or more when TS is 1180 MPa or more, it is judged to have excellent ductility.
[0255] In addition, in the evaluation of the stretch flange formability, a test piece is cut from the center of the plate width, and a hole expansion test is performed with N=3 in accordance with the provisions of the Japan Iron and Steel Federation Standard JFST1001. That is, after a punching tool with a punch diameter of 10mm and a gap of 13% is used to punch a sample of 100mm×100mm square size, a conical punch with a vertex angle of 60 degrees is used to expand the hole with the burr generated when the punching hole is formed on the outside until a crack that penetrates the plate thickness is generated. Based on d0: initial hole diameter (mm) and d: hole diameter when cracks occur (mm) at this time, the hole expansion rate λ(%)={(d-d0) / d0}×100 is calculated, and the average value of the three points implemented is evaluated as λ. Steels with λ of 40% or more are judged to have excellent hole expansion and excellent stretch flangeability.
[0256] Regarding the evaluation of material stability in the board width direction, 23 points (including the board width center position) of the evaluation material were cut from the board width center position (12W / 24 position (W: board width)) at intervals of less than 100 mm from both sides of the board width, and the EL and λ at each position (measurement position X) were calculated. Then, the ratio of the difference between the measured value at the board width center position and each position to the measured value at the center position was calculated to evaluate the material stability in the board width direction.
[0257] Taking EL and λ at the center of the plate width as the reference, the continuous measurement group in which the difference between EL and λ is less than 10% is regarded as the area in which the difference between EL and λ is less than 10%, and the steel having the ratio of this area to the total plate width being 80% or more is judged as having excellent material stability.
[0258] When the plate width of region A satisfying the following formulas (1) and (2) is 80% or more of the total plate width, it is judged that the material stability in the plate width direction is excellent.
[0259] -10≤100×[(EL(%) at measurement position X in area A - EL(%) at center of board width) / EL(%) at center of board width]≤10 …(1)
[0260] -10≤100×[(λ(%) at measurement position X in region A - λ(%) at center of plate width) / λ(%) at center of plate width]≤10 …(2)
[0261] (In the formulas (1) and (2), the measurement positions X are set to a total of 23 locations of the 24-division positions of the plate width W of the steel plate. That is, as positions in the plate width direction, a total of 23 locations including W / 24, 2W / 24, 3W / 24, 4W / 24, 5W / 24, 6W / 24, 7W / 24, 8W / 24, 9W / 24, 10W / 24, 11W / 24, 12W / 24, 13W / 24, 14W / 24, 15W / 24, 16W / 24, 17W / 24, 18W / 24, 19W / 24, 20W / 24, 21W / 24, 22W / 24, and 23W / 24 are set as the measurement positions X.)
[0262] Table 3 shows the measurement results.
[0263]
[0264]
[0265] The examples of the present invention shown in Tables 2 and 3 are excellent in strength, press formability, ductility, stretch flange formability, and material stability in the sheet width direction, whereas the comparative examples are inferior in any of the above items.
[0266] In addition, it can be seen that since the steel plate of the example of the present invention is high-strength and has excellent stamping formability, ductility, extended flange formability and material stability in the plate width direction, the components obtained by forming the steel plate of the example of the present invention, the components obtained by joining, and the components obtained by forming and joining are also high-strength and have excellent stamping formability, ductility, extended flange formability and material stability in the plate width direction as the steel plate of the example of the present invention.
Claims
1. A steel plate having: A composition containing, in mass%, C: 0.05-0.20%, Si: 0.40-1.50%, Mn: 1.9-3.5%, P: 0.02% or less, S: 0.01% or less, sol.Al: 0.005-0.50%, N: less than 0.015%, and the balance being iron and inevitable impurities; and The area ratio of polygonal ferrite is 10% to 57%, the total area ratio of upper bainite, tempered martensite and lower bainite is 40% to 80%, the volume ratio of retained austenite is 3% to 15%, the area ratio of quenched martensite is 12% or less (including 0%), and the steel structure is composed of the remaining structures. The total area ratio of quenched martensite and retained austenite with an aspect ratio of 3 or less and an equivalent circle diameter of 1.6 μm or more is 20% or less relative to the total area ratio of quenched martensite and retained austenite. The C-rich region (S C≥0.5 ) is less than 15% in area.
2. The steel plate according to claim 1, wherein: As the component composition, one or two selected from the group consisting of Ti: 0.1% or less and B: 0.01% or less are contained in terms of mass %.
3. The steel plate according to claim 1 or 2, wherein: The component composition further contains, in mass %, one or more selected from the group consisting of Cu: 1% or less, Ni: 1% or less, Cr: 1% or less, Mo: 0.5% or less, V: 0.5% or less, and Nb: 0.1% or less.
4. The steel plate according to any one of claims 1 to 3, wherein The component composition further contains, in mass %, one or more selected from the group consisting of Mg: 0.0050% or less, Ca: 0.0050% or less, Sn: 0.1% or less, Sb: 0.1% or less, and REM: 0.0050% or less.
5. The steel plate according to any one of claims 1 to 4, wherein The surface has a zinc coating. 6 . A member formed using the steel plate according to claim 1 .
7. A method for producing a steel sheet, comprising hot rolling, pickling and cold rolling a steel slab having a component composition as claimed in any one of claims 1 to 4, and then annealing the obtained cold-rolled steel sheet, wherein: The annealing comprises: A holding step, wherein the cold-rolled steel sheet is heated to an annealing temperature of 750 to 880° C. and is held at the annealing temperature for 10 to 500 seconds; A first cooling step, wherein the first cooling stop temperature is cooled at a first average cooling rate of 2 to 50° C. / s within a temperature range from the annealing temperature to a first cooling stop temperature of 350 to 550° C.; A second cooling step, wherein after staying at a dwell temperature of 350 to 550° C. for 10 seconds or more and 60 seconds or less, the material is cooled to a second cooling stop temperature of 100 to 300° C. at a second average cooling rate of 3 to 50° C. / s; a reheating step, wherein heating is performed from the second cooling stop temperature to a reheating temperature of the second cooling stop temperature+50° C. or higher and 340° C. or lower at an average heating rate of 2.0° C. / s or higher; and A third cooling step, wherein after the reheating step, cooling is performed at a third average cooling rate of 0.05 to 1.0° C. / s while staying in a temperature range from the reheating temperature to 50° C. for more than 100 seconds.
8. The method for manufacturing a steel plate according to claim 7, wherein: In the second cooling step, the surface of the steel sheet is subjected to hot-dip galvanizing or galvannealing while the steel sheet is held at a holding temperature of 350 to 550° C. for 10 seconds or more and 60 seconds or less.
9. The method for manufacturing a steel plate according to claim 7, wherein: After the annealing, the surface of the steel sheet is subjected to electrogalvanizing treatment. 10 . A method for producing a member, comprising the step of subjecting the steel sheet according to claim 1 to at least one of a forming process and a joining process to produce a member.
Citation Information
Patent Citations
Coating method for coarse base material
JP1980015623A
Airtight package for circuit element and its production
JP1983021911A
High-strength steel sheet having excellent elongation and excellent stretch flangeability and process for production of the same
JP2008297609A